Finite Element Analysis and Root Cause Analysis of Wire Rope Failure in STS Cranes - Ariani, Farida; Pulungan, Bgd. Sinomba Pebi Nanda (Talenta Publisher, 2025)
Wire rope is a critical lifting component in Ship-to-Shore (STS) cranes, whose failure can lead to catastrophic system breakdowns, posing significant safety risks and operational losses. This study investigates the root causes of wire rope failure on a 40-ton capacity STS crane. The methodology integrates Root Cause Analysis (RCA) with a Finite Element Analysis (FEA) simulation using ANSYS Static Structural. The analyzed wire rope has a 28 mm diameter, a 6x36 IWRC configuration, and is made of galvanized high-carbon steel. Simulation results under full operational load revealed a maximum von Mises stress of 681 MPa, exceeding the material's yield strength (≈650 MPa), a total displacement of 16 cm, and a critically low safety factor of 0.53. The failure location was identified on the outer strands at the contact points with sheaves, indicating high-stress concentration zones. Furthermore, the calculated Safe Working Load (SWL) for a standard safety factor of 5 was 82.83 kN, which is drastically lower than the 400 kN operational load per rope, confirming severe overstress conditions. The RCA fishbone diagram identified key contributing factors: material specification mismatch, suboptimal sheave design, inadequate maintenance protocols, and insufficient design-stage analysis. The study concludes that the wire rope is unfit for service under current conditions and recommends immediate replacement, revised preventive maintenance schedules incorporating FEA, design optimization of support components, and implementation of real-time load monitoring systems.